Assessment of Nurses' Performance in Caring for Cancer Patients in Kirkuk City: a Cross Sectional Study - Hamdiya Muhammed; Yousif Salih (Indonesian Journal Publisher, 2025)
Cancer is considered one of the major issues in the twenty-first century. It's one of the leading causes of death and a barrier to life expectancy, globally. Its burden expected to increase worldwide from 2020 and throughout the first half of the 21st century. Nurses as one of the medical team are considered at the frontline in mitigating this increasing, through their contributions in patients care with their diversity of care roles and responsibilities in cancer care. This study aimed to assess oncology nurses level of performance in cancer care in Kirkuk City. Methods, a descriptive (cross sectional) design conducted at Oncology and Hematology Center in Kirkuk City, Iraq. An observational checklist used to collect data of 81 nurse in the time line between February 15th, 2025 to March 27th,2025. Results, nurses showed an overall weak adherence to cancer care protocols in general(PGMS=24.28%), where nurses scored low levels in both the